2023
DOI: 10.1097/qad.0000000000003776
|View full text |Cite
|
Sign up to set email alerts
|

The HIV-2 proviral landscape is dominated by defective proviruses

Catherine K. Koofhethile,
Ce Gao,
Charlotte Chang
et al.

Abstract: Background: Compared with HIV-1 infection, HIV-2 infection is associated with a slower progression to AIDS. Understanding the persistence of HIV-2 infection might inform the mechanisms responsible for differences in the pathogenicity of HIV-2 versus HIV-1. Methods: In this study, we analyzed the genetic composition of the proviral reservoir in archived blood samples collected from 13 untreated HIV-2-infected adults from Senegal. We used single-genome, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Most HIV studies are focused on the HIV-1 variant; however, HIV-2 should not be neglected as an estimated 2 million people worldwide are living with this infection, and there might be differences in the mechanisms that regulate HIV-2 persistence and latency. Recently, Koofhethile et al observed that the HIV-2 proviral landscape is dominated by defective proviruses, similar to what happens in HIV-1 infection [142]. Nonetheless, although HIV-2 LTR is similar to HIV-1 LTR, it contains a duplicated TAR RNA stem-loop structure [143] and is less responsive to CD4+ T cell activation signals [144].…”
Section: What Can We Learn From Hiv-2?mentioning
confidence: 88%
“…Most HIV studies are focused on the HIV-1 variant; however, HIV-2 should not be neglected as an estimated 2 million people worldwide are living with this infection, and there might be differences in the mechanisms that regulate HIV-2 persistence and latency. Recently, Koofhethile et al observed that the HIV-2 proviral landscape is dominated by defective proviruses, similar to what happens in HIV-1 infection [142]. Nonetheless, although HIV-2 LTR is similar to HIV-1 LTR, it contains a duplicated TAR RNA stem-loop structure [143] and is less responsive to CD4+ T cell activation signals [144].…”
Section: What Can We Learn From Hiv-2?mentioning
confidence: 88%